Three macrophage subsets are identified in the uterus during early human pregnancy. Issue 12 (December 2018) - Jiang, Xiangxiang; Du, Mei-Rong; Li, Min; Wang, Hongmei
Abstract Macrophages are crucial for a successful pregnancy, and malfunctions of decidual macrophages correlate with adverse pregnancy outcomes, such as spontaneous abortion and preeclampsia. Previously, decidual macrophages were often thought to be a single population. In the present study, we identified three decidual macrophage subsets, CCR2−CD11cLO (CD11clow, ~80%), CCR2−CD11cHI (CD11chigh, ~5%), and CCR2+CD11cHI (CD11chigh, 10–15%), during the first trimester of human pregnancy by flow cytometry analysis. CCR2−CD11cLO macrophages are widely distributed in the decidua, while CCR2−CD11cHI and CCR2+CD11cHI macrophages are primarily detected close to extravillous trophoblast cells according to immunofluorescence staining. According to RNA sequencing bioinformatics analysis and in vitro functional studies, these three subsets of macrophages have different phagocytic capacities. CCR2+CD11cHI macrophages have pro-inflammatory characteristics, while the CCR2−CD11cHI population is suggested to be anti-oxidative and anti-inflammatory due to its high expression of critical heme metabolism-related genes, suggesting that these two subsets of macrophages maintain an inflammatory balance at the leading edge of trophoblast invasion to facilitate the clearance of pathogen infection as well as maintain the homeostasis of the maternal-fetal interface. The present study physiologically identifies three decidual macrophage subsets. Further clarification of the functions of these subsets will improve our understanding of maternal-fetal crosstalk in the maintenance of a healthy pregnancy.